Zhi-Kang-Yin formula attenuates high-fat diet-induced metabolic disorders through modulating gut microbiota-bile acids axis in mice - Yifan Li; Hao Wang; Xiaofang He; Weize Zhu; Yiyang Bao; Xinxin Gao; Wenjin Huang; Xinyu Ge; Wenjing Wei; Huan Zhang; Lili Sheng; Tao Zhang; et al. (BMC, 2024)
Abstract Background Metabolic disorders have become one of the global medical problems. Due to the complexity of its pathogenesis, there is still no effective treatment. Bile acids (BAs) and gut microbiota (GM) have been proved to be closely related to host metabolism, which could be important targets for metabolic disorders. Zhi-Kang-Yin (ZKY) is a traditional Chinese medicine (TCM) formula developed by the research team according to theory of TCM and has been shown to improve metabolism in clinic. However, the underlying mechanisms are unclear. Aim of the study This study aimed to investigate the potential mechanisms of the beneficial effect of ZKY on metabolism. Methods High-fat diet (HFD)-fed mice were treated with and without ZKY. The glucose and lipid metabolism-related indexes were measured. BA profile, GM composition and hepatic transcriptome were then investigated to analyze the changes of BAs, GM, and hepatic gene expression. Moreover, the relationship between GM and BAs was identified with functional gene quantification and ex vivo fermentation experiment. Results ZKY reduced weight gain and lipid levels in both liver and serum, attenuated hepatic steatosis and improved glucose tolerance in HFD-fed mice. BA profile detection showed that ZKY changed the composition of BAs and increased the proportion of unconjugated BAs and non-12-OH BAs. Hepatic transcriptomic analysis revealed fatty acid metabolism and BA biosynthesis related pathways were regulated. In addition, ZKY significantly changed the structure of GM and upregulated the gene copy number of bacterial bile salt hydrolase. Meanwhile, ZKY directly promoted the growth of Bifidobacterium, which is a well-known bile salt hydrolase-producing genus. The ex vivo co-culture experiment with gut microbiota and BAs demonstrated that the changes of BAs profile in ZKY group were mediated by ZKY-shifted GM, which led to increased expression of genes associated with fatty acid degradation in the liver. Conclusion Our study indicated that the effect of ZKY on improving metabolism is associated with the modulation of GM-BAs axis, especially, by upregulating the abundance of bile salt hydrolase-expression bacteria and increasing the levels of unconjugated BAs. This study indicates that GM-BAs axis might be an important pathway for improving metabolic disorders by ZKY.